The lack of cumulative impact analysis in the environmental licensing of the Industrial Port Complex at Pontal do Paraná, on the southern coast of Brazil (Sustainability in Debate, 2022)
The Environmental Impact Assessment is an environmental policy instrument developed in response to societal concerns about the negative impacts of major development projects and the recognition of planetary boundaries. In Brazil, it is part of the environmental licensing process, which also encompasses various weak points. Cumulative Impacts (CIs) from multiple interventions (both natural or anthropic) across specific spaces and time frames are routinely dealt with poorly. The installation of an Industrial Port Complex (IPC) at Pontal do Paraná, a municipality on the south coast of Brazil is currently undergoing an environmental licensing process. This article analyzes five projects’ Terms of Reference (TR) and Environmental Impact Studies (EIS) to verify if and how the IPC projects assessCIs. The results suggest that TRs and EISs provide insufficient to assess CIs. In the political-procedural sphere, there is no institutionalization for Cumulative Impact Analysis. Moreover, even if it is performed,it is essential to consider how power relations affect the public acceptance of mega-projects. Locally, uncertainty about CIs reflects into scenarios of environmental unsustainability.